Aplicação do conceito de logística reversa no processo de scrap de componentes eletrônicos para redução de KPI em uma empresa de montagem de placa SMD do Polo Industrial de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Large companies in the global market seek gains in reducing expenses and achieving their indicators. Therefore, aiming at the company's final profitability, the theme of reverse logistics is increasingly present in this context, seeking alternatives to reduce raw material waste, for example. Among all industrial sectors, industries in the electronics sector present important values in relation to their waste, due to the high value of the components. The Manaus Industrial Pole is a global reference in the electronics assembly sector and this project was carried out in a multinational located there, creating an action plan whose main objective was to reduce the Material Loss Rate KPI by forty percent in the process of SMD, employing a component reuse chain. The methodology used was descriptive research applied through a case study that proved to be assertive for the dissertation. Using the concept of reverse logistics, the factory was able to share a way of feeding back a portion of its raw material process within its own internal chain. The results were satisfactory, therefore, the main objective was achieved, bringing not only compliance within the subsidiary, which served as a laboratory for the idea, but will also serve as a reference for other future projects within the company, in other factories that are part of this multinational.
Keywords: Logística empresarial; Reaproveitamento (Sobras, refugos, etc.); ENGENHARIAS: ENGENHARIA DE PRODUCAO; Eletrônico; Logística reversa; Desperdício; Reuso